PERBANDINGAN KONSENTRASI PROGESTERON SELAMA SIKLUS BIRAHI PADA DOMBA WARINGIN YANG DIINDUKSI PGF2α DAN KOMBINASI PGF2α DAN GnRH - Yezi Gita Rahayu; Tongku Nizwan Siregar; Gholib Gholib; Cut Nila Thasmi; Herrialfian Herrialfian; Razali Daud; Zuhrawati Zuhrawati; Hamdan Hamdan; Rasmaidar Rasmaidar (JURNAL ILMIAH PETERNAKAN TERPADU, 2018)
This study aimed to compare the progesterone concentrations in Waringin sheep estrus cycle which induced by PGF2α or the combination of PGF2α and GnRH. This study used six Waringin sheep those were divided into twice groups, K1 and K2. K1(n=3) were injected by 7.5 mg PGF2α intramuscularly for 10 days, while K2 (n = 3) were injected by PGF2α and GnRH. On the first day K2 were injected by 7.5 mg PGF2α, then followed by injection 50 µg of GnRH on day 8th and re-injected by 7.5 mg PGF2α on day 15th. On day 18th, sample was re-injected using 50 µg GnRH. Waringin sheep those showed estrus symptoms were detected visually and with signs showed by sheep stud. Blood samples were taken on the 7th, 14th, and 21st day after the peak heat. The measurement of progesterone concentration was conducted by enzyme linked immunosorbent assay (ELISA). The results showed those the concentrations of progesterone on day 7th, 14th, and 21st on K1 vs K2 were 1.324±1.079, 7.607±8.922, and 5.220±1.653  vs 4.705±3.369, 4.184±5.512, and 1.797±0.898 ng/mL (P>0,05), respectively. In conclusion, the concentration of progesterone of Waringin sheep after inducing with PGF2α or combination PGF2α and GnRH at different cycle periode did not show differences. Keywords: Estrus Cycle, GnRH, PGF2α, Progesterone, Waringin Sheep